Effects of mechanical inspiration and expiration exercise on velopharyngeal incompetence in subacute stroke patients - Kyung Won Jang; Sook Joung Lee; Sang Beom Kim; Kyeong Woo Lee; Jong Hwa Lee; Jin Gee Park (Medical Journals Sweden, 2018)
Objective: To investigate the therapeutic effects of mechanical inspiration and expiration exercise using mechanical cough assist on velopharyngeal incompetence in patients with subacute stroke. Design: Pilot, randomized controlled study. Setting: University-based rehabilitation centre. Subjects: Thirty-six patients with subacute stroke diagnosed with velopharyngeal incompetence by videofluoroscopic swallowing study. Methods: Subjects were randomly assigned to 2 groups. The study group received conventional dysphagia therapy and additional mechanical inspiration and expiration exercise. The control group received conventional dysphagia therapy only. Swallowing function was evaluated according to the American Speech-Language-Hearing association scale, functional dysphagia score, and the penetration aspiration scale, based on the videofluoroscopic swallowing study. Coughing function was measured using peak cough flow. Results: Eighteen patients in each group completed the protocol and were analysed. After treatment, the study group showed significant improvement in functional dysphagia score with regard to nasal penetration degree. Comparing the treatment effect between the 2 groups, nasal penetration degree and peak cough flow showed greater improvement in the study group. Conclusion: Mechanical inspiration and expiration exercise had a therapeutic effect on velopharyngeal incompetence in subacute stroke patients with dysphagia. This therapy is easy to provide clinically and could be a useful therapeutic strategy for velo-pharyngeal incompetence with dysphagia in patients with stroke.